2005
DOI: 10.1016/j.pcrj.2005.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Switching asthma patients to a once-daily inhaled steroid improves compliance and reduces healthcare costs

Abstract: Objective: To determine the costs and consequences of switching asthma patients, managed in primary care, from a twice-daily inhaled corticosteroid (ICS), to either a once-daily or another twice-daily ICS. Design: This was a case-control study based on an interrogation of the General Practice Research Database in the UK, for patients with a Read code of asthma who were managed between 1990 and 2001, and who had received at least two prescriptions for a twice-daily ICS within 12 months, before switching to a on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
39
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 14 publications
2
39
0
Order By: Relevance
“…13 During regular reviews, almost a third of asthma patients reported not taking their prophylactic medication as prescribed. 16 In other studies, half of patients underused their asthma medication, 17 and even the 50% of people with difficult-tocontrol asthma were not compliant with oral corticosteroids. 7 Even conservative estimates indicate that poor compliance makes an important contribution to the morbidity, mortality and expense associated with asthma.…”
Section: Improving Compliancementioning
confidence: 97%
“…13 During regular reviews, almost a third of asthma patients reported not taking their prophylactic medication as prescribed. 16 In other studies, half of patients underused their asthma medication, 17 and even the 50% of people with difficult-tocontrol asthma were not compliant with oral corticosteroids. 7 Even conservative estimates indicate that poor compliance makes an important contribution to the morbidity, mortality and expense associated with asthma.…”
Section: Improving Compliancementioning
confidence: 97%
“…19 Guest et al specifically investigated the change in adherence when patients with asthma were switched from a twice-daily ICS to once-daily ICS treatment. 11 As might be expected, patients who switched to a once-daily ICS were more likely to be highly adherent and had lower asthma-related charges compared with patients who switched to another twice-daily ICS dosing regimen. 11 In addition, Price et al found that for MF specifically, adherence was significantly higher for once-daily dosing than twicedaily dosing.…”
mentioning
confidence: 76%
“…11 As might be expected, patients who switched to a once-daily ICS were more likely to be highly adherent and had lower asthma-related charges compared with patients who switched to another twice-daily ICS dosing regimen. 11 In addition, Price et al found that for MF specifically, adherence was significantly higher for once-daily dosing than twicedaily dosing. 20 NAEPP guidelines note the importance of assessing and encouraging asthma patient adherence to prescribed therapy, 1 and point out that adherence to a therapeutic plan is enhanced when daily doses are minimized.…”
mentioning
confidence: 76%
See 1 more Smart Citation
“…Therefore, ongoing efforts are aimed at improving the level of treatment adherence in patients with asthma, including the development of ICS that are effective, have a rapid onset of action and are suitable for once-daily dosing. [3,4] Ciclesonide is delivered as a solution to the lung via a hydrofluoroalkane-propelled metered-dose inhaler (HFA-MDI). [5] Pulmonary esterases convert ciclesonide into the active metabolite, desisobutyryl-ciclesonide (des-CIC).…”
Section: Introductionmentioning
confidence: 99%